Palaeoenvironmental evolution from the early Holocene to the present of the Almenara marsh (western Mediterranean) - Blázquez-Morilla, Ana M.; Rodríguez-Pérez, Ana; Sanjuán-Lamata, Daniel (Scientia Marina, 2018)
The main aim of this study is to characterize the different stages in the palaeoenvironmental evolution of the Almenara marsh, Spain, from the early Holocene to the present day. This marsh is one of the most important in Castellón province. Five cores extracted from the marsh underwent sedimentological analysis, micropalaeontological study (foraminifera, ostracods and gastropods) and 14C dating. The results show that before the maximum transgression of the Mediterranean during the Marine Isotope Stage 1 (5500 cal yr. BP dating in the Almenara marsh), the area was occupied by a brackish marsh (prior to the 8.2 ka event). During the middle Holocene, the regional sea level rise and later stability caused an oligohaline/freshwater marsh with fluctuating water levels to form. This marsh occupied the entire area of today’s Almenara marsh at least between 7570 and 2780 cal yr BP. The results may indicate a phase of greater contribution of groundwater inputs (and rainfall/riverine discharge) during the middle Holocene as a response to a climatic phase characterized by higher humidity. Today, the marsh is filled with sediments from natural and anthropic processes related to the agricultural activity carried out throughout the area (except for the central part, which has been reclaimed as wetland). The water of the present-day marsh (like that prior to 8.2 ka event) is brackish, as is indicated by the benthic foraminiferal assemblage; this contrasts with the earlier oligohaline/freshwater marsh determined in the survey cores during the middle Holocene until the time of the Iberian culture.